STUDY ON FOOD AND FEEDING HABITS OF SILVER CATFISH BAGRUS BAYAD IN ZOBE RESERVOIR, DUTSINMA LOCAL GOVERNMENT AREA, KATSINA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Bagrus bayad is an important fresh water fish species with high commercial and economic value in Nigeria. The present study was conducted on Bagrus bayad in Zobe reservoir to ascertain the food and feeding habits of the species. Specimens were obtained on weekly basis from the artisanal fishermen catches at their landing sites at the Reservoir, for a period of four months (April – July, 2017). Data on stomach contents was subjected to frequency of occurrence and Point method analysis. Categorization of the stomach content of the sampled fishes showed that 90.40% had food items, while 9.62% were empty. The result showed that fish and fish parts had the highest occurrence (72.34%). It composed of the bulk diet (27.16%) by volumetric Index (V), and also formed the most important food item (AI) (52.93%). This is an indication that B. bayad exhibited carnivorous feeding habits in the Reservoir.
Keywords: Food and feeding habits, Bagrus bayad, Reservoir, Dutsinma